Pengembangan Paket Wisata Berbasis Potensi Lokal Melalui Pendekatan Partisipatif di Desa Wisata Jatirejo - Nareswari Febrian Putri; Ira Dwi Astuti; Alwa Yumna Ariani; Arselliano Bethsadha Putra; Chrestella Nathania Gusta; Akhmad Iqbal Maulana; Danang Damar Jati; Sarah Anindita; Erica Rich Ratantri; Raden Roro Syahra Kansasabira; Razkyla Wilhelmina Nelissen; Unan Yusmaniar Oktiawati (Direktorat Pengabdian kepada Masyarakat, 2026)
The development of tourism villages requires structured and community-based packaging of local potential to create meaningful and sustainable tourism experiences. Jatirejo Village, Kulon Progo Regency, possesses various cultural and agricultural resources that had not yet been integrated into a coherent tourism package. This community service program aimed to formulate and implement a thematic tourism package to optimize the tourism potential of Jatirejo Tourism Village. A participatory approach was employed through community assistance, collaborative planning, and direct implementation involving university students and local residents. The results indicate that the One Day Tour Pesona Jatirejo tourism package was successfully developed and implemented, integrating cultural performances, cycling tours, agricultural harvesting activities, and local handicraft and culinary workshops. The novelty of this program lies in the direct implementation of the tourism package within a district-level tourism village competition, allowing the designed package to be tested and evaluated in real conditions. This program contributed to strengthening community participation, enhancing local capacity in tourism management, reinforcing local identity, and creating opportunities for sustainable economic development. The developed tourism package is expected to serve as an initial model for the continuous and independent development of tourism activities in Jatirejo Tourism Village.